The Impact of Organizational Change on Organizational Commitment and The Mediation Effect of Job Security, Trust and Justice in Pharmaceutical Industry in Indonesia - Chandra, Kristin Aina; Hendratmoko, Hendratmoko (Jurnal Komunikasi dan Bisnis, 2024)
This research aims to determine the impact of organizational change on organizational commitment and the mediating effect of Job Security, Trust and Justice in pharmaceutical industry in Indonesia. Research was conducted among employees from four (4) different pharmaceutical companies in Jakarta, Indonesia. The sampling technique is based on probability sampling and data collection method used in this research was using questionnaire with total sampel obtained was 108. The research design used is descriptive quantitative research. The data analysis technique uses structural equation modeling-partial least square. The result showed that organizational change has insignificant direct positive impact on organizational commitment, Job Security does not mediate the impact of organizational change to organizational commitment, organizational change has indirect significant impact on organizational commitment through mediator variables Trust and Justice. Trust and Justice fully mediate the effect of organizational change to organizational commitment. Based on the result of the study, it was suggested that pharmaceutical companies to put more emphasis on trust & justice and achieve higher level of trust and justice during organizational change process to increase employee’s commitment.